Household Dependence on the Public Distribution System in Bihar: A District-Level Analysis (Journal of Informatics Education and Research, 2025)
One of India's most important welfare initiatives, the Public Distribution System (PDS), works to guarantee food security for households that are economically disadvantaged.  Its efficacy differs greatly between areas and demographic groupings in spite of numerous revisions.  With an emphasis on the percentage of necessary wheat and rice that is purchased from Fair Price Shops (FPS), this study investigates the factors that contribute to household-level reliance on the PDS in the state of Bihar.  utilising primary data gathered from 384 homes in the Patna, Purnia, and Madhepura districts.  The study investigates the ways in which location, socioeconomic status, and demographics affect the amount of food grain purchased from the PDS. While the average household's rice procurement from PDS represents 37% of its needs, descriptive statistics show that wheat procurement is far lower at 6%, suggesting a discrepancy in the efficiency of grain distribution.  To take into consideration the censored nature of the dependent variable (proportions between 0 and 1), the study uses Tobit regression models.  Age, household size, income, caste, education, occupation, and geography are all significant predictors of PDS dependency, according to the regression results.  It is noteworthy that while educated and OBC households are less likely to purchase grains from FPS, especially wheat, larger, poorer, and older households are more likely to rely on PDS.  The PDS is still an essential safety net, although its impact and reach vary by household and grain variety, according to the study's findings. Enhancing wheat supply chains, lowering obstacles to access, and making sure that worthy households are effectively targeted are some policy ideas.  Maximising the advantages of PDS and attaining inclusive food security in Bihar will require improving grain quality, reducing caste and income-based exclusion, and fortifying distribution infrastructure.